DETERMINANTS OF ROLE PERFORMANCE OF VETERINARY ASSISTANT SURGEONS OF ANDHRA PRADESH - Ratnayake, Talata C (Indian Journal of Dairy Science, 2014)
A Study was conducted to identify the factors affecting role performance of VASs in Andhra Pradesh in India using ex-post facto research design. Data were collected from 220 respondents through pretested interview schedule selecting 20 VASs randomly from eleven selected districts in Andhra Pradesh. The data were subjected to correlation and multiple regressions to determine the factors of role performance. Self rating technique was adopted to measure the role performance using a schedule specially prepared for the study.Â  Results revealed that among the group 43.00 per cent of the respondents were medium performers. Out of 16 independent variables, work motivation, availability of physical facilities, organizational job stress (negative), persistence disposition, participativeness and timeliness of availability were found dominating in estimation of role performance of VASs. It is proposed that administrators need to pay more attention on elements of human resource management strategy especially in terms of awards, rewards and appreciation of their hard work and initiate appropriate measures to improve the facilities and resources of VASs for livestock service delivery to the needy farmers. Therefore, apart from confirming a theoretical proposition, the findings of this study are likely to have significant implication in the development of Animal Husbandry sector